2011
DOI: 10.1007/s00779-011-0472-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and adapting behavior during product interaction to influence affect

Abstract: Sometimes, the way in which we interact with products implicitly communicates how we feel. Based on previous studies on how emotions can be detected and communicated via product interaction, we discuss how an interactive product could influence affect by responding and changing behaviors expressing affect. We discuss the proposal of the affective feedback loop in product interaction by its implementation in the prototype of a pen that senses two implicit behaviors related to restlessness, rock and roll. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The fine-tuning of this loop required an iterative process of trial and error involving the designer and various experts. A final experiment was conducted with the pen, to evaluate whether the pen providing inherent feedforward was considered to be more relaxing than the pen without feedback [6]. Preliminary results suggest that inherent feedforward reduced the heart rate of participants, which could indicate a reduction in stress.…”
Section: Resultsmentioning
confidence: 99%
“…The fine-tuning of this loop required an iterative process of trial and error involving the designer and various experts. A final experiment was conducted with the pen, to evaluate whether the pen providing inherent feedforward was considered to be more relaxing than the pen without feedback [6]. Preliminary results suggest that inherent feedforward reduced the heart rate of participants, which could indicate a reduction in stress.…”
Section: Resultsmentioning
confidence: 99%
“…This is an aspect that requires further investigation. More subtle feedback could potentially lead to fully unaware interaction, as demonstrated by Bruns Alonso et al [1] in their pen experiment, making the learning process rely solely on the perceptual motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, closed loop interactions can be designed into intelligent systems to manage the relations between user's action and product's reaction. Elaborating on this concept Bruns Alonso et al [1] describe a framework on how emotional aspects can be influenced by means of an affective feedback loop [18]. They observed that the stressful behaviors of a user could be affected through haptic feedback provided in a pen.…”
Section: Introductionmentioning
confidence: 99%
“…These works are in turn inspired by devices like the Mind spheres speculative interactive meditation aid and the Relax! pen, a prototype device leveraging implicit interaction for afect modifcation [8,19]. Karlesky and Isbister [33] created two "Fidget Widget" prototypes using the Sifteo platform of connected, sensor-and touch display-enabled blocks to enable "mindless" interactions to selectively infuence cognitive and afective states.…”
Section: Existing Fdgeting Devicesmentioning
confidence: 99%
“…Based on past research into non-instrumental movement driving afective change, there exists an opportunity to not only provide responsive haptic feedback but also "feedforward, " or a predictive and intent-driven "inherent" feedback [8]. This would of course require a precise knowledge of 1) what manifested fdgeting behaviors signify and 2) what stimuli will cause what afective efects (and we already know this to be highly individual).…”
Section: Afect Regulation (Personal and Social)mentioning
confidence: 99%